2023
DOI: 10.1111/exd.14951
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional cohort study on the skin microbiota in patients with different acne durations

Lang Sun,
Qingqun Wang,
Huan Wang
et al.

Abstract: Acne is a chronic disease that often persists for years. Skin microbial communities play an essential role in the development of acne. However, limited information is available about the dynamic patterns of skin microbiota in acne. This study aimed to characterize microbial community changes in skin pores and surfaces of acne patients with varying disease time. In this study, a total of 70 skin samples from 22 subjects were collected and sequenced using 16S rRNA amplicon sequencing. Although microbial composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Additionally, polycyclic aromatic hydrocarbons (PAHs) have the potential to bring about detrimental alterations in the composition and functionality of the skin microbiota [13,14]. This could be associated with acne, as demonstrated by a study on the skin microbiota in individuals with acne, which revealed significant changes in the composition of the skin microbial community throughout the course of the disease [15].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Additionally, polycyclic aromatic hydrocarbons (PAHs) have the potential to bring about detrimental alterations in the composition and functionality of the skin microbiota [13,14]. This could be associated with acne, as demonstrated by a study on the skin microbiota in individuals with acne, which revealed significant changes in the composition of the skin microbial community throughout the course of the disease [15].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…The clinical manifestations encompass a diverse range of acneiform lesions, including comedones, papules, pustules, nodules, and cysts. These are often accompanied by excessive sebum secretion (1)(2)(3). Acne, affecting 9.4% of the global population, ranks as the eighth most prevalent disease worldwide.…”
Section: Introductionmentioning
confidence: 99%